Du poids des contraintes au partage concerté des ressources : quelques témoignages des acteurs centraux de la conciliation travail-famille - Lise Chrétien; Isabelle Létourneau (Perspectives Interdisciplinaires sur le Travail et la Santé)
Starting with the observation that today’s working parents are having increasing difficulty assuming their work and family responsibilities, this paper addresses, through the results of a qualitative study on 30 working parents: 1) the problem situations experienced by working parents regarding the work-family balance, 2) the effects experienced by working parents in dealing with these situations, 3) the expectations of working parents regarding other actors from family, work, community and governmental spheres in overcoming these problem situations. The participants’ statements are analyzed within a holistic work-family balance approach, based on a systemic model that involves a constraint-resource dialectic.